(untitled) (Global Journals of Research in Engineering, 2012)
Many maintenance-scheduling methods have been proposed using conventional mathematical programming methods or heuristic techniques. Heuristic approaches provide the most primitive solution based on trial-and-error approaches. Mathematical optimization based techniques are completely distinct from classical programming and trial-and-error heuristic methods. These techniques have been proposed to solve small maintenance scheduling problems. In this paper we explain the difference between both methods in solving generator maintenance scheduling (GMS) problem.